(untitled) (CIPEEX, 2025)
Brazilian Sign Language (Libras) has greatly benefited from technological advances, fostering inclusion and accessibility for the deaf community. In recent years, various innovations have facilitated the communication and learning of Libras for both deaf and hearing individuals. Apps like Hand Talk and first hand, use artificial intelligence to translate text and audio into Libras, enabling wider access to information. In addition, wearable devices and notification systems using lights and vibrations have been developed to help deaf individuals perceive alerts and calls, increasing their autonomy. Real-time transcription tools, such as the AVA app, allow conversations to be transcribed instantly, making meetings and lectures more accessible. The integration of Libras into digital platforms has also been crucial. Videos on platforms like YouTube and social media enable deaf individuals to share their experiences and knowledge, promoting greater visibility and understanding of deaf culture. Content produced by deaf YouTubers like Kitana Dreams and Gabriel Isaac exemplifies how technology can be used to spread information and artistic expressions in Libras. In the educational field, technology has played a key role. Digital tools for teaching Libras are becoming increasingly common, facilitating learning for both deaf and hearing individuals. These tools range from translation apps to distance learning platforms that use Libras as the medium of instruction. However, despite the progress, there are still challenges to overcome. Digital accessibility is not always guaranteed, and many websites and apps still do not provide adequate support for Libras. Additionally, training qualified professionals to develop and implement these technologies is essential to ensuring their effectiveness and reach. In summary, the relationship between Libras and technology today is marked by significant advances that promote inclusion and accessibility. To further promote advancements in accessibility for the Brazilian Deaf community, an innovative software is being planned to teach Brazilian Sign Language (Libras), thus facilitating the literacy of Deaf individuals in the language as well as encouraging more hearing people to learn Libras. With an intuitive interface, the software will combine explanatory videos, practical exercises, and quizzes to ease the understanding of signs and the practice of communication in Libras. Adapted for various proficiency levels, it will allow users of all ages to develop inclusive communication skills in an efficient and engaging manner, promoting greater integration and accessibility for the Deaf community.